Platão, poeta de uma nova tragédia - Santos, Ademir Souza dos (Universidade Federal de São Carlos, 2018)
The placing of the ποίησις in the Platonic Dialogues raises great controversy. On one hand, the Republic engages in a severe criticism of the art of the poets. On the other, albeit with some restrictions, Plato himself applies poetic elements in the construction of his philosophy, from a rather complex character portrayal to the use of the mimetic resources he seemed to condemn. We propose a more comprehensive view to this apparent antinomy. In order to do so, we establish a connection between Diogenes Laertius’s Lives of Eminent Philosophers and the criticism Schleiermacher later addressed to it. From this starting point, together with the analysis of some dialogues (Republic, Apology, Meno, Protagoras, Symposium), we suggest that Plato, besides being a philosopher, may also be considered a poet. In this context, the mimesis occupies a meaningful role in the Paideia process. Lastly, we also argue that, for the understanding of Plato’s ideas, we should consider the formal, literary aspects of his work, as they cannot be dissociated from the so-called philosophical contents addressed in his dialogues.
Plato, poet of a new tragedy
Keywords: Platão; Homero; Schleiermacher, Friedrich, 1768-1834; Diógenes Laércio; Poíesis; Mimesis; Diegesis; Psykagogía; Plato; Homer; Diogenes Laertius; Psychagogy; CIENCIAS HUMANAS::FILOSOFIA::HISTORIA DA FILOSOFIA